Effectiveness Of Implementing Rehabilitation Of Narcotics Criminals In An Effort To Prevent The Risk Of Recidivism And Overcrowded Residents In Correctional Institutions - Dimas Alseta Putra; Sirajuddin; Sigit Sapto Nugroho (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2026)
Abstract Introduction to the Problem: The implementation of rehabilitation at the Class IIA Madiun Youth Penitentiary is one of the author's chosen locations for research on the rehabilitation process and the inhibiting factors in drug rehabilitation, as stipulated in Law Number 35 of 2009 concerning Narcotics. This research is intended to be an effort to prevent recidivism and inmate overcrowding. Purpose/Study Objectives: The implementation of rehabilitation at the Class IIA Madiun Youth Penitentiary has been effective in preventing overcrowding and recidivism and inhibiting factors for the implementation of narcotics rehabilitation at the Class IIA Madiun Youth Prison. Design/Methodology/Approach: The research approach used in this study is a sociological legal approach. The data sources used are primary and secondary. Primary data in this study will be obtained from interviews and observations of the research subjects and related parties. Secondary data will be obtained from document or literature studies sourced from regulations, journals, books, guidelines, and other sources related to the research topic. Findings: The implementation of this program has been adjusted to several relevant regulations, which will later serve as references and guidelines. Currently, there are obstacles encountered in its implementation. The biggest obstacles lie in regulations and supporting infrastructure for the program. To overcome these obstacles, the Class IIA Madiun Youth Prison has developed a method that will serve as a shared guideline for implementing the rehabilitation of drug inmates. Paper Type: Research Article